PENERAPAN MEDIA FLASHCARD UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS MATERI ENERGI DISEKITAR KITA PADA KELAS III UPT SDN SUMURGUNG 1 - nila putri utami; Wendri Wiratsiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The aim of this research is to improve learning in the field of science by utilizing flashcard media for class III for the 2024/2025 academic year. This research adopts the model from Kemis and Taggart, which consists of planning, action, observation and reflection stages carried out in two cycles. In this study there were 9 children from class III UPT SDN Sumurgung 1. In cycle 1 the results showed a percentage of 33,33% who achieved the KKTP, in cycle 2 the percentage of achievement increased to 88,88% so that the KKTP indicator was successfully met. The gains in cycle 2 showed positive developments from implementation in the previous cycle of 55%. Thus, based on research findings, it is known that the use of flashcard media contributes positively to improving science learning outcomes.